2007
DOI: 10.1002/qsar.200620074
|View full text |Cite
|
Sign up to set email alerts
|

Principal Component Analysis of Catalytic Functions in the Composition Space of Heterogeneous Catalysts

Abstract: The objective of this paper is to identify which combinations of constituents of heterogeneous catalysts are related to which final products from a large combinatorially generated dataset. To this end, data on the composition of catalysts are combined with a set of four catalytic activities, and analyzed using a Principle Component Analysis (PCA). From the first attempt of PCA, a dataset of pentanary-mixed metal oxides, Cr a Mo b Ni cCo d Mn e O x , is visualized on the planes of principal components (PCs) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 13 publications
0
24
0
1
Order By: Relevance
“…This could include groupings from dimensional analysis (Rajan et al, 2009), simple relational features (Kanter and Veeramachaneni, 2015), PCA (Sieg et al, 2006), or some other method. In all cases, care must be taken to avoid incompatible operations (e.g., do not add an atomic radius to an ionization potential).…”
Section: Feature Extractionmentioning
confidence: 99%
“…This could include groupings from dimensional analysis (Rajan et al, 2009), simple relational features (Kanter and Veeramachaneni, 2015), PCA (Sieg et al, 2006), or some other method. In all cases, care must be taken to avoid incompatible operations (e.g., do not add an atomic radius to an ionization potential).…”
Section: Feature Extractionmentioning
confidence: 99%
“…[129] Sieg et al showed with quaternary composition spaces that the proper mathematical modeling of such relationships can be accomplished readily with the help of SVMs, multilevel B-splines, or Kriging ( Figure 11). [130] There have been significant developments in the use of IT tools for HTE.…”
Section: Reviewsmentioning
confidence: 99%
“…For example, principle component analysis has recently been applied to the problem of heterogeneous catalysis using only composition variables as components. 6 The ability to include crystalline phase and fiber texture in this type of analysis would greatly facilitate the discovery of new materials not only for catalysis but also for the broad range of applications conducive to investigation with combinatorial methods. We present a simple configuration for simultaneous measurement of thin film composition, thickness, structure, and fiber texture using high-energy x-ray diffraction ͑XRD͒ and energy-dispersive x-ray fluorescence spectroscopy ͑XRF͒.…”
Section: Introductionmentioning
confidence: 99%